PENGARUH PERBANDINGAN BAHAN DENGAN PELARUT DAN LAMA EKSTRAKSI TERHADAP RENDEMEN DAN KARAKTERISTIK EKSTRAK PEWARNA DARI BUAH PANDAN (Pandanus tectorius) - Frety Yudharini, Gst Ayu Kd; Suryawan W, A. A. P. A.; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2016)
The aims of this study were 1) to determine the effect of ratio between material and solvent and time of extraction on the yield and characteristics of pandanus fruit extract dyes, 2) to obtain the best ratio between material and solvent, and time of extraction to produce yield and characteristics of pandanus fruit extract dyes. This study used a randomized block design factorial with 2 factors, namely the first factor was the ratio of material with solvent consisting of three levels 1: 7, 1: 9, and 1:11; the second factor was the extraction time ( 3 hours, 5 hours and 7 hours). The experiments were grouped into 2 groups based on the time of its implementation, in order to obtain 18 experimental units. Variables observed were yield, total carotenoid content, and color intensity. The results showed that the ratio between material and solvent affected the yield, total carotenoid content, the level of redness (a*), and the level of yellowness, but did not affected the level of brightness. The time of extraction affected the total carotenoid content, the level of redness (a*) and the level of yellownes, but did not affected the yield and the level of brightness. The interaction ratio between material and solvent, and time of extraction affected the total caroteno id content, the level of redness (a*), and the level of yellowness, but did not affected the yield, and the level of yellowness. Ratio between material and solvent (1:11), and 5 hours time of extraction was the best treatment to produce fruit extract dyes  with yield of 2,60%, total carotenoid content of 15,12%, the level of bringhtness (L*) 1,30%, the level of redness (a*)  -0,13, and the level of yellowness (b*) 3,59. Keywords: pandanus fruit, dyes, solvent ratio, time of extraction, carotenoid
Keywords: 105